A thought exercise: thinking through the found poetry of Canadian abortion providers. Issue 3 (3rd July 2017) - Shaw, Jessica; Haney, Carly-Ann
ABSTRACT: This paper focuses on the experiences of a graduate student and a professor who engaged in a thought exercise about found poetry. Through the contemplation of nine found poems that were extracted from the professor's doctoral research on abortion providers, they consider how found poetry can be read, interpreted, and experienced. The potential role of found poetry for social work research and practice is also discussed.